2003
DOI: 10.1089/1540419031361363
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Overweight and Obesity in Turkey

Abstract: The objectives of this study were to determine the prevalence of overweight and obesity in Turkey, and to investigate their association with age, gender, and blood pressure. A crosssectional population-based study was performed. A total of 20,119 inhabitants (4975 women and 15,144 men, age > 20 years) from 11 Anatolian cities in four geographic regions were screened for body weight, height, and systolic and diastolic blood pressure between the years 1999 and 2000. The overall prevalence rate of overweight was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
1
8

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 11 publications
3
28
1
8
Order By: Relevance
“…In our study, abdominal obesity was 17.2% in men and 54.8% in women. Mean values of BMI for the Turkish population have been reported in several population-based investigations in Turkey (Onat et al, 1999a;Satman et al, 2002;Hatemi et al, 2003). In line with our results, these studies showed that BMI was significantly higher in women than in men.…”
Section: Ethnic and Country Differences In Ms Prevalencesupporting
confidence: 92%
See 2 more Smart Citations
“…In our study, abdominal obesity was 17.2% in men and 54.8% in women. Mean values of BMI for the Turkish population have been reported in several population-based investigations in Turkey (Onat et al, 1999a;Satman et al, 2002;Hatemi et al, 2003). In line with our results, these studies showed that BMI was significantly higher in women than in men.…”
Section: Ethnic and Country Differences In Ms Prevalencesupporting
confidence: 92%
“…In line with our results, these studies showed that BMI was significantly higher in women than in men. In addition, abdominal obesity is very common in Turkish women (Onat et al, 1999a;Satman et al, 2002;Hatemi et al, 2003). It appears that, in Turkey, obesity is an important problem in women than in men.…”
Section: Ethnic and Country Differences In Ms Prevalencementioning
confidence: 99%
See 1 more Smart Citation
“…This result is consistent with those of Hatemi et al [24] study which indicated that BMI was positively and significantly associated with systolic and diastolic BP. The results of the present study also showed a positive correlation between the women's BMI and blood glucose.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, a positive moderate correlation was detected between BMI and systolic and diastolic BP values. Similarly, in the study by Hatemi et al (19) performed in 11 provinces, the prevalence of obesity was reported to be 24.6% in women, and a positive linear correlation was reported between BMI and BP.…”
Section: Discussionmentioning
confidence: 58%